2019
DOI: 10.1016/j.pbiomolbio.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The theory of interceptor-protector action of DNA binding drugs

Abstract: The review discusses the theory of interceptor-protector action (the IPA theory) as the new selfconsistent biophysical theory establishing a quantitative interrelation between parameters measured in independent physico-chemical experiment and in vitro biological experiment for the class of DNA binding drugs. The elements of the theory provide complete algorithm of analysis, which may potentially be applied to any system of DNA targeting aromatic drugs. Such analytical schemes, apart from extension of current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…It is seen that as the concentration of the added molecules increases, the HGQ value gradually shifts from a positive control to a negative one, indicating that the functional activity of the cell nuclei is restored. It means that the effect of the added molecules, having different chemical structures, on TPT interaction with nonproliferating cells is exerted generally in a similar way and corresponds well with the same studies reported before for C 60 /FMN/CAF introduced simultaneously with other aromatic biologically compounds (see ref and references therein).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…It is seen that as the concentration of the added molecules increases, the HGQ value gradually shifts from a positive control to a negative one, indicating that the functional activity of the cell nuclei is restored. It means that the effect of the added molecules, having different chemical structures, on TPT interaction with nonproliferating cells is exerted generally in a similar way and corresponds well with the same studies reported before for C 60 /FMN/CAF introduced simultaneously with other aromatic biologically compounds (see ref and references therein).…”
Section: Resultssupporting
confidence: 87%
“…However, stage 1 is assumed to be important only at low concentrations of C 60 fullerene, when the fraction of large clusters is too small to dominate in the net binding effect . Comparison of complexation of TPT with C 60 fullerene against the hetero-complexation of TPT with classical interceptor molecules, FMN and CAF, which are known to modulate the biological effect of TPT in vitro through hetero-association (see ref and references therein), showed a similar spectrophotometric manifestation of these complexations, even more pronounced for TPT-C 60 (if compared by values of equilibrium complexation constants). Taking all this into account, we can conclude that the noncovalent interaction (complexation) of TPT with fullerene clusters can be considered confirmed, thereby providing the physicochemical basis for further analysis of their biological interaction in vitro.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations